Geografska podpora participativnemu upravljanju s porečjem Temenice - Mikolič, Sara (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2024)
Participatory river basin management, which requires the cooperation and active engagement of various stakeholders at different levels (local, sub-regional, national and international), is a key aspect of EU water management policy. In Slovenia, although participatory river basin management is formally advocated, it has not yet been effectively implemented in practise, especially in smaller sub-basins where various river initiatives tend to emerge from the bottom up. This paper examines a geographical approach to participatory management of the karst Temenica River basin. The geographical support focused on a comprehensive geographical analysis of the river basin, identification of key water management challenges, stakeholder analysis and empowerment process, and impact assessment of the participatory activities (2020–2023). The results indicate that significant progress has been made toward participatory management in the pilot area of the upper Temenica River basin. Beyond systemic support, the long-term success of participatory management and its extension to the entire Temenica River basin will depend on the ability of stakeholders to maintain and further develop the networks that have been established.
Keywords: celostno upravljanje porečij; Dinaric Karst; Dinarski kras; hidrogeografija; hydrogeography; integrated river basin management; LEADER/CLLD; ponikalnice; porečja; river basin; sinking karst river; Slovenia; sustainable water management; Temenica; upravljanje z vodami